Observational study of maternal and fetal outcome in obstetric emergencies admitted to tertiary care centre - Singh, Neelima; ., Sreedevi; ., Sushma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Objectives of the current study were to evaluate the risks factors, clinical presentations, the management and maternal and fetal outcome of common obstetric emergencies encountered at Government general hospital Nizamabad, Telangana, from April 2019 to November 2019. Methods: It is an Observational, hospital-based study done department of obstetrics and gynaecology in 160 cases of obstetric emergencies managed in 8 months study period were reviewed. Results: Out of 3000 deliveries there were 160 cases of obstetric emergencies giving a percentage of 5.33%. About 84% had antenatal care and 16% had not taken ANC with perinatal mortality of 91.9% in booked cases. Out of 160 cases of obstetric emergencies, obstetric haemorrhage constituted 94 (58.75%) cases and among those cases, 23 cases (24.5%) were PPH including both atonic and traumatic, abruptio placenta constituted 35 cases (37.3%). Out of 160 cases of obstetric emergencies, obstructed labour constituted 29 cases (18.1%) being a frequent indication for emergency caesarean section, 1 case of septic abortion and 30 cases eclampsia. 29 perinatal deaths giving the perinatal mortality rate as 181 per 1000 live births. One maternal mortality due to rupture uterus. Maternal morbidity was in the form of wound infections which was found in 6 cases (3.75%), wound gaping in 2 cases (1.25%) PPH in 19 cases (11.81%), septicaemia in 17 cases (10.6%), puerperal pyrexia 6 cases (3.7%), vaginal or cervical injury 6 cases (3.7%), ICU admissions in 9 cases (5.6%). This morbidity increased the number of days of hospital stay to the patients. Conclusions: In majority of cases, the complications are preventable and treatable with proper antenatal and intranatal care. Identification of high risks cases, education of people about the importance of supervised pregnancy, delivery and emergency obstetric care will reduce the maternal mortality and morbidity and perinatal mortality and morbidity significantly.